A retrospective study of B19 positive antigen blood donations - Mercês, A (2012)
Between August and December 2000 using ID-Parvovirus B19 – DiaMed, we studied 708 blood donations to detect b19 Ag on the plasma kept in our serum colletion, we found a prevalence of 0,424% positive donations. Globoside, a P blood group antigen, is the major red blood cell receptor used by b19 for attachment and entry into the cell. This is why we have included it in our study. We performed the retrospective study in this blood components: Obtained results in blood donors (see poster). Obtained results of transfused patients with blood components from those donors (see poster). Conclusions: As it is possible to see in our results, one of the patients was infected recently by one blood unit. Our objective is not to transfuse this positive blood components to patients in risk, like individuals with underlying haemolytic disorders, immunocompromised patients, immunodeficient individuals, pregnant women, fetus and newborns. Other measures may be implemented, like: deferral permanently those donors, or researche P Ag in all patients?